The Difficulties which Face Public Basic School Principals in Jarash Governorate in Editing Formal Letters and Correspondence and Means of Dealing With These Problems as Perceived by Them (Journal of the College of Education for Women, 2019)
This study aimed at identity baying the difficulties which face public basic schoolprincipals in jar ash governorate in editing formal letters and correspondence and means ofdebating with these problems to collect data the researchers developed a question air wereestablished the population of the study which represents its sample consisted of 129 principals65 males and 64 femalesThe results of the study revealed that the principals face difficulties in office and filemanagement in preparing plans and reports and writing formal letters and answering themsaved recommendations were presented among which were organizing training sessions andworkshops to train the principals on how to dead with there problems.Keywords: difficulties formal correspondence letter editing